Yonyou 2013 - McFarlan, F. Warren (SAGE knowledge. Cases., 2016)
In January 2013, Yonyou Software, the largest management software company in Asia-Pacific, unfolded its three-year business strategy to step up platform development. Following its decade earlier transition from financial software to management software, Yonyou's three-year business strategy was again a business model revolution. This book details Yonyou's plans.